1995
DOI: 10.1074/jbc.270.42.24858
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Leader Sequence Coding Region in Expression and Assembly of Bacteriorhodopsin

Abstract: Bacterio-opsin is made as a precursor in Halobacterium halobium, which has 13 additional residues at the amino terminus. The codons for these residues have been proposed to form a hairpin structure in the mRNA and play a role in ribosome binding; the leader peptide sequence also has been proposed to have a role in membrane insertion of bacteriorhodopsin (BR). We have made mutations in the bop gene region coding for the leader sequence and expressed the mutant genes in an H. halobium mutant lacking wild-type BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
55
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…Xu et al [33] recently demonstrated that bacteriorhodopsin made without a 13 residue leader peptide was properly assembled in the membrane. However, deletion of the leader region resulted in an unstable m R N A and almost no bacteriorhodopsin production.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [33] recently demonstrated that bacteriorhodopsin made without a 13 residue leader peptide was properly assembled in the membrane. However, deletion of the leader region resulted in an unstable m R N A and almost no bacteriorhodopsin production.…”
Section: Discussionmentioning
confidence: 99%
“…However, J774 macrophages internalize and degrade both matrix-retained and non-retained SMase-aggregated LDL, which are mediated partially by LRP (32). The size of SMaseaggregated LDL (ϳ100 nm) would be too small to elicit a phagocytic response (19,58). Ö örni et al observed that SMasetreated aggregated and fused LDL bound to human aortic proteoglycans more tightly in the affinity column than native LDL (20,54).…”
Section: Discussionmentioning
confidence: 99%
“…Xu and Tabas (19) showed that in the presence of a very small amount of SMase (10 milliunits/ml), the endocytosis of LDL was enhanced and led to an increase in LDL degradation and cholesteryl ester accumulation in J774 and mouse peritoneal macrophages. SMase-treated LDL has been shown to be bound and degraded at higher rates than control LDL in a variety of cell lines, including HepG2 cells (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, inflammation plays an important role in atherogenesis (13)(14)(15)(16)(17), and, given the evidence cited above, ASM-mediated ceramide signaling may be responsible for certain inflammatory responses in the developing lesion, such as smooth muscle cell proliferation (25) and apoptosis of macrophages and smooth muscle cells (26,27). Second, one of the products of the ASM gene-secretory SMase (SSMase; see below)-has been linked directly to extracellular subendothelial lipoprotein aggregation, an event that promotes both retention of lipoproteins in the arterial wall and macrophage foam cell formation (25,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
mentioning
confidence: 99%